PENGARUH INTELLECTUAL CAPITALTERHADAP KINERJA PERUSAHAAN - Nabila, Alma Diva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This study aims is to examine the effect of intellectual capital on company performance. Intellectual capital isdetermined byValue Added Intellectual Capital(VAIC) method comprising three component:human capital efficiency, structural capital efficiency, and capital employed efficiency.Whilst, company performance is determined by earnings per share (EPS). This study uses data from companies registered in LQ45 index between 2017-2019. The purposive sampling utilized in this study acquires 78 observable data from 26 companies, which is then analyzed through multiple regression to test the hypotheses. The result of the study indicate that structural capital efficiency and capital employed efficiency have positive effect on company performance.Keywords : Intellectual Capital, VAIC, Firm Performance, EPS, LQ45